Analysis of The Lag in Work Performance of Private Higher Education Lecturer Compared to State Higher Education Lecturer in Indonesia - Wahyuningsih, Sri; Shamsudin, Abdul Shukor; Sahim, Aswin Naldi (International Journal of Economics Studies, 2024)
The State and the private universities in Indonesia are categorized as one of the national instruments to improve the quality of life in the community, nation and state. Meanwhile, the work performance of private university lecturers is quite lagging compared to lecturers in state universities. Although improving the quality of higher education cannot be separated from the improvement of the quality of its main resources, namely lecturers, with the main task of Tri Dharma; teaching, research and service to the community.This study examines the influence of organizational culture factors, individual characteristicistics, and lecturer competence on the achievement motivation and work performance of lecturers at private higher educations in Indonesia, in which achievement motivation and individual characteristic as mediator variables for the relationship between organizational culture and work performance. A total of 100 questionnaires were distributed to the research locations, and all of them were returned completely filled in, and could be processed using PLS Smart4 Structural Equation Modeling statistics. The results of the study show that organizational culture factors, individual characteristic and achievement motivation have direct, positive and significant influence on the work performance of lecturers at private higher educations in Indonesia. In particular, organizational culture also has direct and significant influence on competence, individual characteristic and achievement motivation. However, achievement motivation is partial mediator for the relationship between organizational culture and lecturer work performance. Meanwhile, individual characteristic are partial mediators of the relationship between organizational culture and work performance. Meanwhile, lecturer competency is partial mediator for the relationship between organizational culture and lecturer achievement motivation. With this, it can be understood why there is lag in the achievements of lecturers at private higher educations compared to lecturers at state higher educations in Indonesia. It is hoped that this research can contribute to government policy and academic literature to improve the work performance of lecturers at private higher educations in Indonesia.